Analysis of Generation Regimes in a Technological Gyrotron with a Magnetically Shielded System in the Angel Software Environment - Semenov, E. S.; Proyavin, M. D.; Morozkin, M. V.; Zuev, A. S.; Kamensky, M. V. (Radiophysics and quantum electronics, 2023)
The paper is devoted to a comparison of the results of an experimental study of a 28 GHz/25 kW gyrotron with a magnetically shielded system and the results of calculating the electron–wave interaction with the use of the ANGEL software code on the basis of a self-consistent model with an unfixed radio-frequency field structure. The good agreement between the results confirms the validity of using the developed code for creation of new gyrotrons. Comparison of various experimental data with the calculation results for the electron–wave interaction as well as for electron optics makes possible implicit reevaluation of the actual values of some important gyrotron parameters (the electron pitch factor, transverse velocity spread, etc.).